Red clay mini bricks with nano-bentonite (Clamib-Naben): Materials in early learning / Norizzati Ibrahim ... [et al.] - Ibrahim, Norizzati; Kamaruding, Musmuliadi; Bakhary, Nor Azmi; -, Atiqah Najwa; Wan Abdullah, Wan Zukri; Badrul, Nur Arafah (Research Management Institute (RMI), 2023)
The Ministry of Energy, Science, Technology, Environment, and Climate Change (MESTECC) is concerned about a downward trend (from 48 % in 2012 to 44 % in 2019) of students in schools pursuing Science, Technology, Engineering, and Mathematics (STEM) subjects in schools and higher education institutions. This downward trend may be related to the thinking of the younger generation, who consider engineering courses quite challenging due to the nature of the courses, which are considered "difficult courses". Therefore, the purpose of this research is to explore the effect of implementing red Clay Mini Bricks with Nano-Bentonite (ClaMiBNaBen) materials on anxiety towards engineering among students at the preschool level. A cooperative learning method was utilised among students in developing building models using ClaMiB-NaBen. In order to achieve the objectives of the study, a total of 50 students from pre-school were selected. Observations and pre- and final tests were used to collect empirical data based on practical activities in the class. The data were described using frequency, mean, and standard deviation. The pre-test showed that the majority of students were not interested in the field of engineering. However, the post-test results revealed a significant increase in interest in this field. Therefore, ClaMiB-NaBen is expected to be able to change the perception of the younger generation to be more interested in engineering, which is in line with the Sustainable Development Goals (SDG) of Malaysia that are to be achieved by 2030, as all countries are racing to produce new science and technology that is sustainable, affordable, and safe.